Screening of Elaeocarpus floribundus fruit extracts for bioactive phytocomponents and antibacterial activity against food-borne bacteria - Sircar, Bijayanta; Mandal, Shyamapada (International Journal of Research in Medical Sciences, 2017)
Background: Medicinal plants possess several active components having antimicrobial activity. This study was undertaken to explore the antibacterial activity of Indian olive, Elaeocarpus floribundus, fruit extracts against potential food-borne bacterial isolates. Methods: The ethanolic extracts of olive seed (OSE) and mesocarp-epicarp (OMeE), and the aqueous extracts of olive seed (AqOSE) and mesocarp-epicarp (AqOMeE) were prepared, and analysed qualitatively for phytochemicals. The antibacterial activity of the extracts against food-borne pathogenic bacteria: Bacillus sp., Bacillus cereus, Enterococcus sp. and Corynebacterium sp., was determined by agar-well diffusion method, and minimum inhibitory concentration (MIC) values by agar dilution method. Results: The concentration dependent activity of the extracts against the bacteria was recorded with zone diameter of inhibition 6 - 28 mm for ethanolic extracts, and 7 - 23 mm for aqueous extracts. The ethanolic extracts were confirmed positive for the presence of cardiac glycosides, anthraquinone glycosides, steroids, terpenoids and quinones, while cardiac glycosides, anthraquinone glycosides, steroids, terpenoids, quinones and phenol were detected in the aqueous extracts. The MICs of OSE and OMeE ranged 9.375-12.5mg/ml, and 1.875 - 3.125 mg/ml, respectively, for the test bacteria. Conclusions: The olive fruit extracts contained various bioactive components, and had excellent antibacterial activity against food-borne bacteria. The plant might be useful in the preparation of non-antibiotic antibacterial agents and in the storage of food as well.